Reasons and outcomes for patients receiving ICS/LABA agents prior to, and one month after, emergency department presentations for acute asthma. (2nd September 2019) - Villa-Roel, Cristina; Borgundvaag, Bjug; Majumdar, Sumit R.; Emond, Marcel; Campbell, Sam; Sivilotti, Marco; Abu-Laban, Riyad B.; Stiell, Ian G.; Aaron, Shawn D.; Senthilselvan, Ambikaipakan; Rowe, Brian H.; ,
Abstract: Objective : Asthma is a common emergency department (ED) presentation. This study examined factors associated with inhaled corticosteroids/long-acting beta-agonist (ICS/LABA) use; and management and outcomes before and after ED presentation. Methods : Secondary analysis of a prospective cohort study; adults treated for acute asthma in Canadian EDs underwent a structured interview before discharge and were followed-up four weeks later. Patients received oral corticosteroids (OCS) at discharge and, at physician discretion, most received ICS or ICS/LABA inhaled agents. Analyses focused on ICS/LABA vs "other" treatment groups at ED presentation. Results : Of 807 enrolled patients, 33% reported receiving ICS/LABA at ED presentation; 62% were female, median age was 31 years. Factors independently associated with ICS/LABA treatment prior to ED presentation were: having an asthma action plan; using an asthma diary/peak flow meter; influenza immunization; not using the ED as usual site for prescriptions; ever using OCS and currently using ICS. Patients were treated similarly in the ED and at discharge; however, relapse was higher in the ICS/LABA group, even after adjustment. Conclusion : One-third of patients presenting to the ED with acute asthma were already receiving ICS/LABA agents; this treatment was independently associated with preventive measures. While ICS/LABA management improves control of chronic asthma, patients using these agents who develop acute asthma reflect higher severity and increased risk of future relapse.